Long-term exposure to air pollution raises circulating levels of proprotein convertase subtilisin/kexin type 9 in obese individuals. (April 2019) - Macchi, Chiara; Ferri, Nicola; Favero, Chiara; Cantone, Laura; Vigna, Luisella; Pesatori, Angela C; Lupo, Maria G; Sirtori, Cesare R; Corsini, Alberto; Bollati, Valentina; Ruscica, Massimiliano
Aims: Exposure to airborne particulate matter has been consistently associated with early death and increased morbidity, particularly raising the risk of cardiovascular disease. Obesity, one of the leading cardiovascular disease risk factors, increases susceptibility to the adverse effects of particulate matter exposure. Proprotein convertase subtilisin/kexin type 9 has been related to a large number of cardiovascular risk factors, e.g. atherogenic lipoproteins, arterial stiffness and platelet activation. Thus, the present study was aimed at evaluating, in a series of obese individuals, the effects of particulate matter less than 10 µm in diameter (PM10 ) on proprotein convertase subtilisin/kexin type 9 circulating levels. Methods and results: In 500 obese subjects, participating in the cross-sectional Susceptibility to Particle Health Effects, miRNAs and Exosomes (SPHERE) study, we evaluated the effects of long- and short-term PM10 exposure on circulating proprotein convertase subtilisin/kexin type 9 levels. In the studied individuals (body mass index: 33.3 ± 5.2 kg/m 2 ) with an annual average PM10 exposure of 40.12 ± 4.71 µg/m 3, proprotein convertase subtilisin/kexin type 9 levels were 248.7 ± 78.6 ng/mL. In univariate analysis, PM10 exposure (annual average) was associated with proprotein convertase subtilisin/kexin type 9 levels (β=1.83, standard error = 0.75, p = 0.014). Interestingly, in a multivariable linear regression model, this association was observed only for carriers of lower concentrations of interferon-γ, whereas it was lost in the presence of higher interferon-γ levels. Proprotein convertase subtilisin/kexin type 9 levels were positively associated with the Framingham Risk Score, which was raised by 15.8% for each 100 ng/ml rise of proprotein convertase subtilisin/kexin type 9. Conclusions: In obese individuals, more sensitive to the damaging effects of environmental air pollution, PM10 exposure positively associates with proprotein convertase subtilisin/kexin type 9 plasma levels especially in those with low levels of interferon-γ.